High-Resolution MR Imaging of the Parasellar Ligaments - Mark, Ian T.; In, Myung-Ho; Kang, Daehun; Stinson, Eric; Huston, John; Shu, Yunhong; Leonel, Luciano; Celda, Maria Peris (American Journal of Neuroradiology, 2025)
SUMMARY: The parasellar ligaments have been previously described in cadaver specimens and intraoperatively, but identification on MR imaging has eluded radiologists. Using high-resolution T2-weighted MR imaging, we identified the parasellar ligaments as T2-hypointense, bandlike structures that emanate from the medial wall of the cavernous sinus. Subsequent dissection of the same specimen provided matching anatomic images of the parasellar ligaments identified on MRI. This imaging finding is important because resection of the medial wall of the cavernous sinus has been tied to improved outcomes for gross total resection and endocrinologic remission of functioning pituitary adenomas.MWCSmedial wall of the cavernous sinusNEXnumber of excitations